CESifo World Economic Survey May 2013 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe (CESifo World Economic Survey, 2013)
World Economic Climate: World economic climate improves slightly - Economic Expectations: Economic expectations remain positive - Inflation: Price increases expected to slow down further - Currencies: US dollar expected to rise moderately - Interest Rates: Only slight increase in long-term interest rates expected - Special Topic: World Trade Agenda initiative
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies